2012
DOI: 10.5402/2012/475751
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hybrid Polypropylene-Steel Fiber Addition on Some Hardened Properties of Lightweight Concrete with Pumice Breccia Aggregate

Abstract: Lightweight concrete application in construction field is growing rapidly in these recent years due to its advantages over ordinary concrete. In this paper, pumice breccia which can be found abundantly in Indonesia is proposed to be utilized as the coarse aggregate. In spite of its benefits, lightweight concrete exhibits more brittle characteristics and lower tensile strength compared with normal concrete. On the other hand, fiber addition into concrete has become widely used to improve its tensile properties.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…In similar studies in the literature, it was reported by researchers that the compressive strength results of PP fiber reinforced concrete were obtained in a similar way and that the low strength of the fibers in compression decreased the compressive strength of the concrete [2,4,5]. Widodo et al used steel fiber along with PP fiber to increase compressive strength and achieved better results in compressive strength by balancing the density difference [19]. When flexural test results were examined, it was found that there was a more negligible improvement in the flexural strength of fiber reinforced concrete compared to concrete without fiber addition.…”
Section: Mechanical Testsmentioning
confidence: 77%
See 2 more Smart Citations
“…In similar studies in the literature, it was reported by researchers that the compressive strength results of PP fiber reinforced concrete were obtained in a similar way and that the low strength of the fibers in compression decreased the compressive strength of the concrete [2,4,5]. Widodo et al used steel fiber along with PP fiber to increase compressive strength and achieved better results in compressive strength by balancing the density difference [19]. When flexural test results were examined, it was found that there was a more negligible improvement in the flexural strength of fiber reinforced concrete compared to concrete without fiber addition.…”
Section: Mechanical Testsmentioning
confidence: 77%
“…According to to the researchers, the increasing fiber rate in the concrete mixtures, flexural strength and compressive strength was increased by addition of fibers to concrete. In similar studies carried out around the world, the production of M24 type PP fiber reinforced magnesium-phosphate cement composites for quick repair applications [14], dynamic properties of concrete slabs reinforced with M19 type PP fiber by 0.1% and 0.5% [15], comparison of the properties of reinforced concrete which changes depending on PP fiber dimensions [18], effects of the use of PP-Steel fiber on the hardening properties and impact resistance of concrete [19,20], usability of PP fiber with recycled aggregate 483 [21], effects of PP fibers on the properties of reinforced concrete structures [22][23][24], effects of inorganic additives and surface modified PP fibers on rheological, thermal, thermomechanical and mechanical properties of concrete [25], effect of PP fibers on the burning property of concrete [26], determination of an ideal PP fiber ratio for improving compressive and flexural strength of concrete [27], statistical analysis of PP fiber reinforced concrete [28], reinforcing of concrete and cement mixtures with M5, M10, M15, M24 type PP fibers [29] were investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lightweight aggregate concrete containing mono and triple fiber showed higher splitting and flexural strengths when compared with double hybrid fibers. Widodo et al [8] examined the effect of hybrid polypropylene-steel fiber on properties of lightweight concrete made of pumice breccia as coarse aggregate. Monofilament Polypropylene with 12 mm length and 18 μm diameter and macro hooked end steel fiber with 60 mm length and 0.75mm diameter were used.…”
Section: Introductionmentioning
confidence: 99%
“…Prathap and Siva Reddy [19] conducted an experiment on the elastic modulus by changing the steel fiber content in fiber-reinforced concrete and reported that by increasing the fiber content, the elastic modulus would be increased. Widodo et al [20] investigated the effect of adding the compound (polypropylene and steel) fibers on mechanical properties of concrete and reported that adding the compound fibers would lead to the increase in compressive strength, elastic modulus, tensile strength, and modulus of rupture by 22, 24, 222, and 187%, respectively.…”
mentioning
confidence: 99%